An assessment of the hydro-electric potential of the upper Chao Phraya River Basin - Mabini, Teofilo P.; Prof. Chai Muktabhant; Dean Tomas H. Evens; Prof. Alan D. Benham (Bangkok : SEATO Graduate School of Engineering, 1961)
The thesis outlines Thailand's present status in the assessment and production of waterpower, refers to the evident need for an overall estimate as a guide in economic planning, then surveys the most important factors bearing upon the production of hydroelectric power in the headwaters of the Upper Chao Phraya River, an area of 106,470 kmp2 (Bcomprising 20.5 percent of the total area of Thailand. The international standards used, first in the assessment of gross rainfall potential, then through successive stages to technically exploitable and economic potential, are defined. The methods used in assessing the various potentials for the Upper Chao Phraya River Basin are described fully. The net economic potential of the region is estimated at 570,000 kW on 100 percent load factor, equivalent to 5,000 million kWh per annum. Taking into account Thailand's present and foreseeable future load growth, this will suffice to meet the demand of domestic and industrial consumers till about 1990 if resources outside the Chao Phraya River remain undeveloped in the meantime.s
A thesis submitted in partial fulfillment if the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Thesis (M.Eng.) - SEATO Graduate School of Engineering
Keywords: Water-power electric plants -- Chao Phraya River